Spectrum of oral lesions in a tertiary care center of Nepal - Acharya, Sudeep; Pradhan, Amita; KC, Shivraj; Mahato, Moni; Acharya, Sandhya Chapagain (Journal of Chitwan Medical College, 2021)
Background: Lesions in the oral cavity may be of variety of types. Their trends are also increasing day by day. The aim of the study was to determine the spectrum of oral lesions reporting at the tertiary care center in Nepal. Methods: A retrospective study was conducted among from the medical records among the samples sent for biopsy from the department of Oral and Maxillofacial Surgery at KIST Medical College from a period of 2008 to 2017 AD. The data was entered into excel and transferred into SPSS version 16 and analyzed using descriptive statistics presented in the form of table. Results: A total number of 84 cases were include into the study. Age of the patients were ranged from 7 to 87 years. Oral mucosa was the most common site followed by tongue. The most common lesion reported was pyogenic granuloma followed by well differentiated oral squamous cell carcinoma. Conclusions: The majority of the oral cavity lesions are diverse in nature. All lesion especially in the oral cavity should be biopsied to rule out malignancy. Diagnosis of any of these rare lesions is important from the management point of view.